Remittance Inflow, Digital Technology, and Human Development Index in Sub-Saharan Africa - Onyia, Chinedu Callistus; Okereke, Samuel Felix; Onodu, Ebere (PT Mattawang Mediatama Solution, 2025)
Personal remittances an important source of external finance to many households and countries in Sub-Saharan Africa have been hampered by cost of transfers of these funds, amidst advancement in digital technologies. This study examines the combined effect of remittance inflow and digital technology on human development index in Sub-Saharan Africa. The study employed the conditional panel quantile regression methods and a panel data of forty-five (45) SSA countries covering the period 2010 to 2022 for data analysis. The findings of this study revealed that the effect of remittance and digital technology on human development index varies across SSA countries with base on their human development index (HDI) level. The study also found that the interaction effect of remittance and digital technology on human development index has noticeable variations across the lower HDI (25th quantile), middle HDI (50th quantile) and higher HDI (75th quantile) levels. These effects of remittance and digital technology on human development index together their interaction is higher for countries at the middle HDI level (50th quantile). The study therefore recommends that to boost personal remittance inflow from abroad for improvement in human development index amidst advancement in digital technologies, Sub-Saharan African countries should introduce consumer oriented digital platforms for remittance services which should be adequately protected. The study therefore, concludes that as remittances from abroad are becoming major sources of foreign financial inflows, harnessing the drivers of these remittance inflows is vital for improvement in the human development index in SSA.